Neutral Lipids of Oats Fruit (Avena Sativa L.) - N. K. Yuldasheva; S. D. Gusakova; D. Kh. Nurullaeva; N. T. Farmanova; R. P. Zakirova; E. R. Kurbanova (Разработка и регистрация лекарственных средств, 2020)
Introduction. Lipids are a widespread group of biologically active substances in nature, making up the bulk of the organic substances of all living organisms. They accumulate in plants in seeds, as well as in fruits and perform a number of vital functions: they are the main components of cell membranes and the energy reserve for the body.Aim. Study of neutral lipids of sown oats (Avena sativa L.).Materials and methods. The objects of the study were fruits (grains) of oats of the sown variety "Tashkent 1," harvested in the Republic of Uzbekistan. Results and discussions. Neutral lipids of oat grains have been found to contain 13 fatty acids with a predominance of the sum of oleic, linolenic and linoleic acids. The total degree of unsaturation was almost 78%. Absorption bands characteristic of these substances were observed in the IR spectrum of MEGC.Conclusion. According to the results of the NL analysis, oat grains consisted of triacylglycerides and free LCDs, which were accompanied by hydrocarbons, phytosterols, triterpenoids and tocopherols.